Higher disease activity and lower renal function in patients with rheumatoid arthritis are associated with loss of muscle mass: results from a long‐term follow‐up study. Issue 3 (9th June 2020) - Nogi, Shinichi; Hashimoto, Atsushi; Tohma, Shigeto; Matsui, Toshihiro
Abstract: Background: Muscle mass or strength is an important factor of activities of daily living in patients with rheumatoid arthritis (RA). However, there are few reports analysing the long‐term change in muscle mass in these patients. The aim of this study was to examine the relationship of patient's background or disease activity of RA with change in muscle mass after 7 years. Methods: Muscle mass was measured in 101 female patients with RA in 2010. Among them, 79 patients underwent remeasurements in 2017. We examined the relationship between muscle mass at baseline in 2010 or changes in muscle mass (i.e., the difference between 2010 and 2017 or the ratio of 2017 to 2010) and the patients' background, disease activity of RA, treatment, or renal function. Logistic regression analysis was used to explore the factors associated with loss of muscle mass. Muscle mass was evaluated by bioelectrical impedance analysis. Results: At baseline in 2010, the age (mean ± SD) of 101 patients was 62.6 ± 9.8 years. Muscle mass measurements in 2010 showed a significantly negative correlation with patient age ( r = −0.361, p < 0.001), Modified Health Assessment Questionnaire (mHAQ) ( r = −0.461, p < 0.001), and Disease Activity Score (DAS)28‐CRP ( r = −0.249, p = 0.013). Mean (±SD) muscle mass was not significantly different between 2010 (32.5 ± 3.4 kg) and 2017 (32.1 ± 3.8 kg). Changes in muscle mass (the difference or ratio) were negatively correlated with the mean value of DAS28‐CRP for 7 years ( r = −0.281, p = 0.012 or r = −0.298, p = 0.010, respectively) and positively correlated with the estimated glomerular filtration rate (eGFR). However, they were not correlated with the use of glucocorticoids, age, or mHAQ. Logistic regression analysis showed that a mean DAS28‐CRP value for 7 years >2.6 (odds ratio (OR): 3.49; 95% confidence interval (CI): 1.2–11.1; p = 0.028) and eGFR≤80 in 2010 (OR: 3.42; 95% CI: 1.2–11.1; p = 0.030) was significantly associated with >5% loss of muscle mass after 7 years. Conclusions: Patients with higher disease activity of RA and lower renal function exhibited a tendency toward loss of muscle mass after 7 years.